Perceptions of Customers' towards Online Shopping: An Empirical Study - Sharma, Geeta (Gyan Management Journal, 2013)
In globalization epoch, electronic marketing is a great rebellion. The growing use of Internet in India provides a developing vision for online shopping. 1/ e-marketers know the factors affecting on/ine Indian behavior, and the relationships between these factors and the type of on line buyers, then they can further develop their marketing strategies to transform potential customers into active ones, while retaining existing online cusl'omers. Over the last decade maximum business organizat:ions are running with technological change. Retailers are formulating strategies to meet the demand of online shoppers; they are busy in studying consumer behavior in the field of online shopping, to see the consumer attitudes towards on line shopping. The objective of the study is to examine the behaviour of customers, their perceptions about online shopping. Structured questionnaire was administered to measure the perceptions about online shopping and solicit responses on a five point likert scale, ranging from strongly disagree to strongly agree. Independent sample t-test, A NOVA, was undertaken. Findings have implications for the organizations to improve their dealing with customers as per their perceptions.
Keywords: e-tailing; customer perceived risk; traditional/physical shopping; global phenomenon